Adoption of Persuasive Technology as a Communication Media for Learning in Integrated Schools - Pasaribu, Sara Debora Uli; Susilo, Daniel; Girsang, Lasmery RM (Universitas Veteran Bangun Nusantara, 2024)
In the current era, persuasive technology is increasingly being used in the health and wellness field to help users improve their lifestyle and find information about their health problems. Along with the rapid development of science and technology in this digital era, the field of education is also experiencing the same thing. This research was conducted to examine the use of persuasive technology adoption in the education domain. Along with the rapid development of Information and Communication Technology (ICT) in this digital era, the field of education is also experiencing technological advances and developments that bring innovation to education. This can be seen from the many digital platforms used by schools to support learning such as Google Classroom, Noosphere, Zoom, Canva For Education, Smart Library, etc. This research uses a descriptive qualitative method with a post-positivist approach. Research data were obtained from interviews, observations, and studying supporting documents/data. Interviews were conducted with informants, namely teachers and curriculum developers. The theories used in this research are the Media Richness Theory (MRT) and the Technology Acceptance Model (TAM). This study concludes that the adoption of persuasive technology that has been implemented by Pahoa Integrated School has been running effectively. In practice, the persuasive technology applied by Pahoa Integrated School has been able to accommodate the communicator (teacher), and the medium (application) to communicants (students). This research can make a real contribution, especially in the field of education at large, so that persuasive technology can be effectively integrated into learning.